Establishment methods and research progress of livestock and poultry immortalized cell lines: A review - Guo, Dongxue; Zhang, Li; Wang, Xiaotong; Zheng, Jiahui; Lin, Shudai (Frontiers in Veterinary Science, 2022)
The infinite cell line is one of the most favored experimental tools and plays an irreplaceable role in cell-based biological research. Primary cells from normal animal tissues undergo a limited number of divisions and subcultures in vitro before they enter senescence and die. On the contrary, the infinite cell line is a population of non-senescent cells that could proliferate indefinitely in vitro under the stimulation of external factors such as physicochemical stimulation, virus infection or transfer of immortality genes. Cell immortalization is the basis for establishing an infinite cell line, and previous studies have found that methods to obtain immortalized cells mainly included physical and chemical stimulation, heterologous expression of viral oncogenes, increased telomerase activity, and spontaneous formation. However, some immortalized cells do not necessarily proliferate permanently, despite their can extend lifespan compared with primary cells. The infinite cell line not only avoids the complicated process of collecting primary cell, but also provides a convenient and reliable tool for studying scientific problems in biology. At present, how to establish a stable infinite cell line to maximize the proliferation of cells while maintaining the normal function of the cells is a hot issue in the biological community. This review briefly introduces the methods of cell immortalization, discusses the related progress of establishing immortalized cell lines in livestock and poultry, and compares the characteristics of several methods, hoping to provide some ideas for generating new immortalized cell lines.